DEVELOPMENT OF AUTOMATIC STORAGE AND INVENTORY MANAGEMENT SYSTEMS IN ENGINEERING - Turaev Tirkash Turaevich; Uraimov Muhammaddiyor Bohodir coals (Zeta Repository, 2023)
The development of automatic storage and inventory management systems in mechanical engineering is a hot topic that attracts the attention of many manufacturing companies. Automation of these processes can greatly improve production efficiency, improve product quality and reduce production costs.